(untitled) (Economics and region, 2017)
UDC 330.341 Vitalii Svichkar, PhD (Economics). Poltava National Technical Yuri Kondratyuk University. World Financial System: Problems and Perspectives of Reforming. The article is devoted to the process of reforming the world financial system and world economic organizations since the foundation of the International Monetary Fund at the Bretton Woods Conference in 1944. The aim of the article is to analyze the problems and perspectives of the world financial system reforming to avoid financial crises. Special attention is given to the results of cooperation of the IMF and the «Group of Twenty» during the world financial crisis 2008-2009. The article mentions the main stages of the historical development of the world financial system: foundation of the Bretton Woods financial system, rejection of the gold standard at the Jamaica Conference, transition to the floating exchange rates, the wave of crises in the 1990-s, the world financial crisis of 2008-2009. The process of evolution of the IMF within the framework of these global events is considered. The cooperation of the IMF, the «Group of Twenty» and the EU is considered. The reforms of the IMF and their results are analyzed. The policy of the IMF at different historical stages of its evolution is estimated. Especially is marked the necessity of the further reforms of the IMF for better adaptation to changes in modern financial system. Keywords: International Monetary Fund, international economics, world financial system, financial crisis, G-20, IMF reforming, EU.